2017
DOI: 10.17159/sajs.2017/20160364
|View full text |Cite
|
Sign up to set email alerts
|

Teacher participation in science fairs as professional development in South Africa

Abstract: This research was undertaken to understand the perceptions of the Physical Sciences teachers who participate in the South African ‘Eskom Expo for Young Scientists’, regarding the educational significance of the science fair, and the extent to which expo participation provides an opportunity for professional development. The educational significance of this article is found in its contribution to the professional identity of teachers in their roles as organisers, mentors and judges. The model of Beijaard et al.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 20 publications
1
3
0
4
Order By: Relevance
“…The lack of resources has been documented as disadvantaging learners (Flanagan, 2013;Gifford & Wiygul, 1992;Mbowane, Villiers & Braun, 2017). The results of this study concur with previous studies that the poor quality of judges affects their competence and that some judges are biased (Atkins, 2014;Bernard, 2011).…”
Section: Engagementsupporting
confidence: 90%
“…The lack of resources has been documented as disadvantaging learners (Flanagan, 2013;Gifford & Wiygul, 1992;Mbowane, Villiers & Braun, 2017). The results of this study concur with previous studies that the poor quality of judges affects their competence and that some judges are biased (Atkins, 2014;Bernard, 2011).…”
Section: Engagementsupporting
confidence: 90%
“…Hechter (2011) showed that integrating subject matter content and contextualized pedagogic methods in courses results in improved perceptions of science teaching efficacy. Mbowane et al (2017) showed that teacher participation in science fairs can contribute to the building of pedagogical knowledge, content knowledge (both procedural and declarative or factual knowledge), and pedagogical content knowledge. Moreover, according to these authors, planning and participating in a science fair can improve self-efficacy beliefs, develop strengthened, positive attitudes towards science, and strategies of inquiry-based learning and effective methodological instruction, which can contribute to the participants' school-based teaching.…”
Section: Discussionmentioning
confidence: 99%
“…Partisipasi guru baik secara parsial maupun simultan memiliki pengaruh terhadap implementasi rencana kerja madrasah. Partisipasi guru membantu memastikan koordinasi keputusan yang lebih besar antara guru dan kepala sekolah (Mbowane et al, 2017).…”
Section: Salahunclassified